(untitled) (World Science, 2020)
Resume. The experience of providing medical care during the anti-terrorist operation in eastern Ukraine has shown that in the structure of modern combat surgical trauma gunshot wounds with soft tissue defects are 64.9-68.2%, of which 36.4-37.5% small and medium, 28.5-30.7% are large and very large defects. Goal: To improve the results of surgical care for soft tissue defects by introducing differentiated surgical tactics for wound closure to each level. Material and methods. The total amount of the study was 136 wounded with shrapnel, bullet and explosive injuries from April 2014 to September 2018. Determination of surgical tactics for closing soft tissue defects was performed on the basis of metric classification, taking into account the area, volume and anatomical areas of the lesion. Results. The combination of metric characteristics of wound defects by area, volume and location of wounds in a single classification allowed to offer a comprehensive approach to sorting the wounded by the level of medical care and determine further reconstructive surgical tactics to close soft tissue defects. Conclusions. The introduction of differentiated surgical tactics in wounded with gunshot defects of the soft tissues at the all levels of medical care improved functional results: the proportion of satisfactory increased from 46.9% to 53.7%, the relative number of unsatisfactory decreased from 18.8% to 11.6%